Person-centered practice in the Portuguese healthcare system: A documentary study - Diana Vareta; Elaine Santana; Célia Oliveira; Cristina Baixinho; Filipa Ventura (PLoS ONE, 2026)
Background Person-centered practice has increasingly become a key structural component of health systems, driving the progressive reformulation of public health policies internationally. Despite broad consensus regarding its importance, its integration into clinical practice continues to face significant challenges. The Person-Centred Practice Framework identifies the macro context as a critical domain for sustainable implementation, as it encompasses the structural and strategic factors that shape healthcare delivery. Objective To characterize the person-centered practice framing within the macro context of the Portuguese healthcare system. Methodology Qualitative, descriptive, and retrospective documentary study. A systematic literature search was conducted on the websites of entities responsible for defining, guiding, and regulating healthcare in Portugal. Using predefined eligibility criteria, 40 documents were selected. Textual analysis was performed using IRAMUTEQ® software and guided by the constructs of the macro context domain of the Person-Centred Practice Framework. Results The lexicometric analysis identified five classes, grouped into two thematic fields: i) Structural and organizational determinants of person-centered practice , comprising the classes Systemic vision and integrated response , Organizational culture and participation , Digital transformation and information management , and Political vision and governance structures ; and ii) Operationalization of person-centered practice , represented solely by the class Care approach , reflecting its thematic specificity. Factorial analysis revealed distinct and poorly connected discursive patterns associated with different action levels within the healthcare system. Similarity analysis highlighted a discourse centered on the health-care-person nucleus, showing relations with service organization, care integration, and person participation, albeit with word dispersion suggesting misalignment between organizational and practice levels. Conclusion The macrocontextual framing of person-centered practice in the Portuguese healthcare system demonstrates significant political and strategic advances, as seen in the emphasis on humanized care, investment in health literacy and digitalization, and the introduction of Integrated Care Pathways. However, implementation remains limited due to the absence of clear formative guidelines, biomedical paradigm persistence, and lack of evaluation mechanisms sensitive to care experience.